O conceito vigotskiano de compensação na narrativa clínica de Oliver Sacks - Palhuzi, Bárbara Caroline Celestino (2020)
This present research is a theoretical-conceptual study, which aimed to investigate how and if Vygotsky's concept of compensation, from his Defectology studies, appears in Oliver Sacks’ clinical narrative; for this particularly investigation, the studies on deafness present in his “Seeing Voices: A Journey Into the World of the Deaf” (1989) book. A bibliographic survey was conducted to gather related works to the topic in hand and the selection of Sacks studies for analysis. It presents the systematization of the compensation’s discussion, exposing the first uses of the concept and its conceptions in different areas of knowledge; Vygotskian definition of compensation and the presentation of this author's Defectology, in which the concept in question is used, with Alfred Adler's studies as the most direct reference for formulating the concept. The core of this work's systematization is composed by: a brief Sacks’ biographical introduction; the description and analysis of his studies on deafness, present previously mentioned book, and the comparison of all these with the theorizations about compensation and Defectology developed by Vygotsky. At this point of the research, were analyzed the approximations of the discussions and investigations made by Sacks with the elaborations present in the psychology of Vygotsky and his working partner, Luria, with whom Sacks maintained an intense epistolary exchange. As a result, the compensation’s concept, as well as some language’s concept defended by Vygotsky, appear in Sacks' studies. However, their presence is intertwined in Sacks' clinical practice, which incorporates them, guiding them to his area of knowledge, neurology. In addition, other categories such as historicity and totality, foundations of the historical-cultural psychology’s method - even if it was not intentional - were present in several, or almost all, studies by Sacks by the investigative movement of his research. A very important idea of this research is that the compensation’s concept refers to a constant struggle for humanization; it is, therefore, the conditions (material and symbolic) made possible by culture to meet the needs of the subjects, arising from organic deficiencies, thus preventing the unfolding of a deficiency of a second order caused by the absence of these conditions. Finally, it is understood, from this research, that the use of the compensation’s concept is indispensable as a basis in the development of alternative ways for education, especially for children with disabilities